Analisis Kesulitan Siswa dalam Membaca Lancar Kelas II Sekolah Dasar - Mardhiyyah, Ainul; Zulhaq, Febrinaldi; Rahmawati, Vanny; Chandra, Chandra; Wijanarko, Tiok (Lembaga Yasin AlSys, 2024)
This research aims to describe the characteristics of difficulties in reading fluently and the factors that influence students’ reading fluency in class II. This research was conducted on second grade elementary schoo students. The type of research used is descriptive qualitative. The data collection techniques used by researchers in this research were oral tests, interviews, observation, and documentation. The research focus in this study was on second grade elementary school students and their parents. The result of the research show that the characteristics of difficulty reading fluently in class II are mispronouncing words and sentences, reading spelling, omitting letters and words, adding words, flat voice intonation and not paying attention to punctuation, not being able to put words together, letters blend together, halting reading, no expression in reading and not understanding the content of the reading. Factor causing difficulty in reading fluently are internal and external factors. Internal factors include (lack of familiarity with letters, omotting letters and words, lack of interest in reading, and physical factors). Meanwhile, external factors include (family emvironmental factors).